Fatores de risco para a transmissão zoonótica da esporotricose no município de Belo Horizonte/MG: um estudo de caso-controle - Maria Paula Vieira Rodrigues (2024)
Sporotrichosis is a subcutaneous mycosis caused by dimorphic fungi of the Sporothrix schenckii complex. It has a cosmopolitan, emerging character and is considered a neglected disease. In Brazil and Minas Gerais, it is related to zoonotic transmission between felines and humans. This study aimed to identify activities and risk factors associated with the occurrence of sporotrichosis in the city of Belo Horizonte/Minas Gerais. A case-control study was carried out, with 63 human cases and 126 total controls, distributed across regions. The cases were extracted from notifications of human occurrences between the years 2016 and 2022, and the controls were guided by the addresses of the cases. Through a semi-structured questionnaire, sociodemographic data, data on animals, the environment and knowledge of the disease were obtained. Samples from animals with suspicious lesions were collected and sent for diagnosis, and study participants received information about the disease at the end of the interview. The human population showed improved trends in sociodemographic aspects. There was a significant difference between the Barreiro and Oeste Regions and the others, and a significant association between being a woman and being a case (p ≤0.05). In a multivariate analysis of animal and environmental data, the variables that showed a statistically significant association were: having already had a cat with sporotrichosis (p=0.000), having exposed soil in the residence (p=0.002) and cleaning the yard daily (p =0.015), reinforcing the importance of the human-animal-environment triad in the epidemiology of the disease. Regarding data on knowledge about the disease, there was a significant association between being a case and having knowledge about sporotrichosis, demonstrating a lack of information among the general population about this disease before becoming infected. Health education is a key element in changing the population's behavioral factors, and thus preventing the spread of the disease. More investments must be made in this sense, including the need for more targeted and culturally sensitive health education strategies, adapted to the specific needs of each public and community. It is believed that this work may have contributed in this regard, providing reliable information that can guide and assist public authorities in making decisions and investments, and that may have helped in the dissemination of accurate information about sporotrichosis in Belo Horizonte. As far as we know, there is still no case-control study that focuses mainly on sporotrichosis.